Geology and rockmass condition of Dhulikhel-Panchkhal area, Kavre District, Central Nepal Lesser Himalaya - Paudel, Prem Nath; Tamrakar, Naresh Kazi (Bulletin of the Department of Geology, 2013)
A geological mapping was carried out and the rock mass characteristics of the Lesser Himalayan rocks distributed in the Dhulikhel-Panchkhal area (Kavre Distric) were studied along with their physical and mechanical properties. The lithological units distributed in the study area belong to the Benighat Slate of the Upper Nawakot Group and the Bhimphedi Group as separated by the Chak-Rosi Thrust. The lithological units strike NW-SE and dip southwards forming the eastern closure of part of the northern limb of the Mahabharat synclinorium. The area comprises mainly micaceous quartzite, psammitic schist, metasandstone and metasiltstone. Micaceous quartzite is a rock type of the Kalitar Formation, Chisapani quartzite and the Markhu Formation. The Markhu quartzite is slightly calcareous. Psammitic schist is a rock type of the Kulekhani Formation and the Markhu Formation. Metasandstone and metasiltstone are the rock types of the Tistung Formation. The rock masses consist mainly of three to four major joint sets including the joint parallel to foliation. The discontinuity characteristics indicate that the rocks are blocky in nature, and nearly smooth to rough surface with soft filling aperture. The rock mass is nearly fresh, indurated and stiff. The slopes are influenced by stable and unstable wedges, plane and toppling failures. The rock masses are classified into fair to good rock classes according to rock mass rating system. DOI: http://dx.doi.org/10.3126/bdg.v15i0.7412 Bulletin of the Department of Geology, Vol. 15, 2012, pp. 1–14